Relative Forecast Accuracy and the Timing of Earnings Forecast Announcements - Hassell, John M.; Jennings, Robert H. (The Accounting Review, 1986)
[Previous studies concerning the relative accuracy of management and financial analyst earnings forecasts have produced conflicting conclusions. Resolving this conflicting evidence is important because of the role relative accuracy potentially plays in such issues as the imposition of mandatory management forecast disclosures, the information content of management versus analyst forecast releases, and the motive of management in providing earnings forecasts to the market. Using weekly consensus (mean) financial analyst earnings forecasts, we document a close association between relative forecast accuracy and the timing of the release of the forecasts. We find that management forecasts issued subsequently to, coincidentally with, and up to four weeks prior to analyst forecasts are significantly more accurate than the analysts' estimates. The consensus analyst forecasts are more accurate beginning the ninth week after the release of the management forecast. Thus, by more closely controlling for the timing of the analysts' forecasts, we are able to provide a more precise picture of the dynamic nature of relative forecast accuracy.]